2015
DOI: 10.1017/s1368980015000476
|View full text |Cite
|
Sign up to set email alerts
|

An obesogenic island in the Mediterranean: mapping potential drivers of obesity in Malta

Abstract: Objective: The prevalence of childhood and adult obesity in Malta is among the highest in the world. Although increasingly recognised as a public health problem with substantial future economic implications for the national health and social care systems, understanding the context underlying the burden of obesity is necessary for the development of appropriate counter-strategies. Design: We conducted a contextual analysis to explore factors that may have potentially contributed to the establishment of an obeso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…This concept was firstly used in 1996 (“obese” means excess of corporal fat and “genic” refers to production or synthesis) [93]. Currently, the obesogenic environmental is defined as “the addition of the influences that have the environments, the opportunities or the living conditions to promote the obesity in individuals or populations” [94]. These influences promote the consumption of high levels or energy as well as diets based on non-healthy food (fast food, take away meals, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…This concept was firstly used in 1996 (“obese” means excess of corporal fat and “genic” refers to production or synthesis) [93]. Currently, the obesogenic environmental is defined as “the addition of the influences that have the environments, the opportunities or the living conditions to promote the obesity in individuals or populations” [94]. These influences promote the consumption of high levels or energy as well as diets based on non-healthy food (fast food, take away meals, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The interest in the relationship between the built environment and physical activity levels among the elderly population has grown steadily over the past years, resulting in a substantial increase in studies on this topic across the world [ 13 ]. In general, studies of the accessibility of public open spaces (POS) and their influence in physical activity are predominantly from Australia, UK and USA [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], while in the Mediterranean setting, this topic has been the subject of a limited number of studies [ 22 ]. This has resulted in a gap of information and the need to investigate within the Mediterranean context separately which different types of POS are associated to physical activity since low CVD risk and longevity has often been associated to the Mediterranean life style without taking into account intrinsic factors such as their surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…24 It was noted that the food environment, like in other countries, including within high-educational institutions, is bombarded with high sugar, fat and salt food. 25,26 Furthermore, it has been reported that low vegetable and fruit intake along with the high intake of sugar and salt resulted in one in five deaths in 2017 among the Maltese population. 27 It is also a cultural norm in Malta to indulge in a large meal portion size as well as the tendency to engage in feasts and celebrations with abundance of food and drink typically high in saturated fats and sugars.…”
Section: Discussionmentioning
confidence: 99%